The Dong Xa Shroud. (October 2014) - Cameron, Judith
It is generally recognized that archaeological textiles are amongst the most difficult organics to recover from archaeological sites and many fragments are lost during excavations. This article discusses the 2004 excavations of Dongson textiles preserved through waterlogging in irrigation canals at the site of Dong Xa in northern Vietnam.